Back to the future. - Cook, William; Allardice, Lisa (New Statesman, 2003)
Discusses the way that the sci-fi TV show "Dr. Who" reflected the social cultural history of Great Britain. Television shows whose stories mirrored the socio-economic conditions of the time in which they were made; "Dr. Who" actors who epitomised their respective eras; Declining popularity; National Film Theatre which celebrate's the show's 40th anniversary.